RELEVANSI TEORI KRIMINOLOGI KONTROL SOSIAL TERHADAP PELAKU KASUS TINDAK PIDANA BERULANG (RECIDIVIS) NARKOBA - Sinta Dewi Pramudita, Wahyu; Toufiqurrahman, Thoriq (Cahaya Ilmu Bangsa, 2025)
Recidivism is a serious phenomenon in many countries, including Indonesia. The theory of social control criminology provides a relevant framework for understanding the factors that influence drug recidivism and designing effective coping strategies. This study aims to examine the relevance of the theory of social control criminology to cases of drug violations or recidivism. The research method used in this study is the normative juridical method to analyze the relationship between the theory of social control criminology and drug residue. The results of the study indicate that there is a strong correlation between the theory of social control and cases of drug recidivism. Social ties such as family, friends, and the environment play an important role in preventing drug recidivism. Positive social support can help people stay away from drug use. In addition, self-control also plays an important role in preventing drug-related crimes. Individuals who are able to control negative desires and urges, such as the desire to use drugs, are generally better able to avoid re-engaging in criminal activities. Environmental factors also have a significant impact on the spread of drugs. Therefore, efforts are needed to support positive behavior.